The future of taxation in changing labour markets - Michael Christl; Ilias Livanos; Andrea Papini; Alberto Tumino (European Commission, Joint Research Centre (JRC), 2022)
This paper provides a first assessment of the fiscal and distributional consequences of the ongoing structural changes in the labour markets of EU Member States, mostly driven by technological progress and ageing. Cedefop 2020 Skill forecasts, EUROSTAT population projections and the forecast on pension expenditures from the 2021 Ageing Report depict a scenario of an ageing population, an inverted U-shaped unemployment trend and potentially polarising labour markets, the latter mostly driven by a surge in high-skill occupations. This analysis makes use of the microsimulation model EUROMOD and reweighting techniques to analyse the fiscal and distributional impacts of these trends, given the current tax-benefit policies. The results suggest that the macro trends will increase pressure on government budgets. The analysis also shows evidence of the capacity of the current tax-benefit systems to counterbalance the increases in income inequality and poverty risks triggered by the expected future labour markets developments.
Keywords: J11; J21; H68; 330; income distribution; budget; deficit; job polarisation; population ageing